1991
DOI: 10.1101/gad.5.12b.2481
|View full text |Cite
|
Sign up to set email alerts
|

Control of Drosophila wing and haltere development by the nuclear vestigial gene product.

Abstract: The Dipteran flight appendages, the wings and halteres, develop from larval imaginal discs that also produce other sections of the second and third thoracic adult body segments. Loss of vestigial (vg) function in Drosophila selectively eliminates wing and haltere formation. Here, we show that vg expression is spatially restricted to the presumptive wing and haltere regions of these imaginal discs. An intronic regulatory element mediates this restriction and may elaborate upon cues that activate vg expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
222
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(227 citation statements)
references
References 27 publications
5
222
0
Order By: Relevance
“…40,41 In addition, the fact that vg is highly expressed in the same area and is absolutely required for wing pouch development, led us to monitor cell death regulators expression in both wild-type and vg null / þ discs. 7 Using aminopterin, we showed that VG and DHFR are required for the integrity of wing margin cells, in addition to cell proliferation. A decrease in both products, induces specific rpr expression, DIAP1 downregulation and caspase-mediated cell death at the D/V boundary of the wing disc.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…40,41 In addition, the fact that vg is highly expressed in the same area and is absolutely required for wing pouch development, led us to monitor cell death regulators expression in both wild-type and vg null / þ discs. 7 Using aminopterin, we showed that VG and DHFR are required for the integrity of wing margin cells, in addition to cell proliferation. A decrease in both products, induces specific rpr expression, DIAP1 downregulation and caspase-mediated cell death at the D/V boundary of the wing disc.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the complete loss of wing tissue in vg null homozygous mutant 7,11 and the impossibility to recover vg null clones 4,36 are probably due to both proliferation impairment and apoptosis triggering. The requirement for DHFR during both processes raises the possibility of mutual cross-talk between cell survival and proliferation that would rely on VG function and DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endogenous expression patterns of wg and dpp in the wing disc during the second and early third larval instars. vg (cross-hatched) is expressed where wg and dpp signals intersect and is required for proper wing and haltere development (Williams, Bell, & Carroll, 1991).…”
Section: Fig 2 Transdetermination Events In Drosophila Imaginal Discsmentioning
confidence: 99%
“…These indirectly activate decapentaplegic between the two compartments, establishing a gradient moving out from a central stripe in the wing [16]. Similarly, dorsal and ventral wing surfaces are defined by expression of apterous and vestigial, respectively, in the second instar [17,18]. This is just part of a complex network of interacting genes that establishes spatial information.…”
Section: Early Wing Development In the Flymentioning
confidence: 99%